(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
Republic of Macedonia is the candidate-member state of the EU and has started its High Level Accession Dialogue (HLAD), therefore it is of essential interest to harmonize its national criminal legal system to the EU law. In this article the author elaborates the impact of the EU’s Directive 2014/42/EU considering the European framework for freezing and confiscation of instrumentalities and proceeds of crime in the European Union to the Macedonian criminal justice system. The level of transposition and harmonization of this EU Directive into Macedonian legal system is evaluated through the steps from the ongoing reform of the Macedonian criminal justice system. Hence, the author will examine the current Macedonian legal framework together with the Macedonian courts’ practice regarding the implementation of the existing legal provisions for freezing, confiscation and recovery of the assets, together with the elaboration of the possible limitations and reasons for infrequent use of these measures by the Macedonian courts. In this fashion the author will detect the most common problems particularly with the question of the impact of the time limitation of the freezing of the assets during the criminal procedure, and will provide possible solutions for improvement of the national legal framework.